Focal nodular hyperplasia combined with hepatocellular carcinoma with bone metastasis: a case report and literature review - Zhang, Yuliang; Deng, Xiyue; Cao, Kaiyue; Li, Yang (Frontiers in Oncology, 2025)
Focal nodular hyperplasia (FNH), the second most common benign liver lesion, is widely regarded as having no malignant potential. This study reports a 29-year-old male who was admitted to the hospital due to a space-occupying liver lesion accompanied by low back pain. Abdominal contrast-enhanced computed tomography (CE-CT) suggested FNH. The patient underwent surgical treatment, and postoperative pathological results revealed both FNH and hepatocellular carcinoma (HCC). The patient still experienced low back pain symptoms after surgery. He was later confirmed to have bone metastasis (BM) and received radiotherapy. Cases combining FNH and HCC are extremely rare, particularly when accompanied by metastasis. This study aims to report a case of FNH combined with HCC and accompanied by BM, and to review its treatment process in detail.